EXAMINING FACULTY AND STAFF PERCEPTIONS OF ENERGY USE AT NAZARBAYEV UNIVERSITY - Butt, Khadija; Naiman, Alikhan; Ussina, Nazym (Nazarbayev University Graduate School of Public Policy, 2025)
The study analyzes the faculty and staff perception of energy-saving behavior at Nazarbayev University. Using a mixed-methods approach, 54 survey responses were collected and analyzed using descriptive and inferential statistics, whereas 12 semi structured interviews were conducted and analyzed through content analysis. The survey and interview respondents shared their awareness of sustainable energy use, factors influencing energy conservation, and the barriers faced in reducing energy consumption in their daily activities on campus. The research is structured around the Theory of Planned Behavior to assess how its components of Personal Attitude, Subjective Norm, and Perceived Behavioral Control influence energy use behavior. The research findings revealed that Personal Attitude is a significant factor influencing faculty and staff energy conservation practices, whereas Subjective Norms and Perceived Behavioral Control had a weak correlation with the energy-saving behavior of faculty and staff at Nazarbayev University. The results show that faculty and staff have low awareness of energy conservation initiatives at the university. Policy recommendations based on international experience are provided for the Nazarbayev University administration to promote sustainable energy-saving behavior among faculty and staff through reduced communication gaps, integrated sustainability culture into the workplace, and implemented desired engagement and incentive initiatives. The next step of the research is to expand the sample size and conduct an inter-organization comparison to understand whether similar energy-saving behavior exists beyond Nazarbayev University. Future studies are encouraged to apply the extended theory of planned behavior or alternative behavior models and improve the measurement of perceived behavioral control by separating the internal and external factors.
Keywords: Energy conservation; Faculty and staff behavior; Theory of Planned Behavior; Higher Education Sustainability; Type of access: Embargo